MDP-1: A novel eukaryotic magnesium-dependent phosphatase - J. Selengut; Levine, R. L. (BiochemistryBiochemistry, 2000)
We report here the purification, cloning, expression, and characterization of a novel phosphatase, MDP-1. In the course of investigating the reported acid phosphatase activity of carbonic anhydrase III preparations, several discrete phosphatases were discerned. One of these, a magnesium-dependent species of 18.6 kDa, was purified to homogeneity and yielded several peptide sequences from which the parent gene was identified by database searching. Although orthologous genes were identified in fungi and plants as well as mammalian species, there was no apparent homology to any known family of phosphatases. The enzyme was expressed in Escherichia coli with a fusion tag and purified by affinity methods. The recombinant enzyme showed magnesium-dependent acid phosphatase activity comparable to the originally isolated rabbit protein. The enzyme catalyzes the rapid hydrolysis of p-nitrophenyl phosphate, ribose-5-phosphate, and phosphotyrosine. The selectivity for phosphotyrosine over phosphoserine or phosphothreonine is considerable, but the enzyme did not show activity toward five phosphotyrosine-containing peptides. None of the various substrates assayed (including various nucleotide, sugar, amino acid and peptide phosphates, phosphoinositides, and phosphodiesters) exhibited K(M) values lower than 1 mM, and many showed negligible rates of hydrolysis. The enzyme is inhibited by vanadate and fluoride but not by azide, cyanide, calcium, lithium, or tartaric acid. Chemical labeling, refolding, dialysis, and mutagenesis experiments suggest that the enzymatic mechanism is not dependent on cysteine, histidine, or nonmagnesium metal ions. In recognition of these observations, the enzyme has been given the name magnesium-dependent phosphatase-1 (MDP-1).
http://www.ncbi.nlm.nih.gov/pubmed/10889041?dopt=Abstract
Keywords: Amino Acid Sequence; Animals; Catalysis; Cations; Chromatography, Affinity; Cloning, Molecular; Cysteine; Enzyme Inhibitors; Histidine; Hydrogen-Ion Concentration; Magnesium; Mice; Molecular Sequence Data; Phosphoprotein Phosphatases; Protein Phosphatase 1; Rabbits; Sequence Analysis, Protein; Sequence Homology, Amino Acid; Substrate Specificity